Surface modification of Mg/Al layered double hydroxide by camphorsulfonic acid doped polyaniline and its applications for anticorrosive coating. (25th June 2018) - Du, Peng; Liu, Chengbao; Qiu, Shihui; Liu, Guangzhou; Zhao, Haichao
Abstract: Although Mg/Al layered double hydroxide has significant anion exchange capability and hydrophobicity, its layer-blocking performance is rarely investigated for anti-corrosive performance. In this work, the camphorsulfonic acid doped polyaniline(CPANI)-modified Mg/Al layered double hydroxide (LDH) composites were successfully prepared through oxidative polymerization with an aim to improve dispersion of hydrotalcite in waterborne epoxy resin. Through a series of basic characterizations, camphorsulfonic acid doped polyaniline was successfully coated on the surface of layered double hydroxide and its dispersibility in water was greatly improved. In addition, the CPANI modified LDH was pigmented into waterborne epoxy resin to form a composite coating, further, potentiodynamic curve and electrochemical impedance spectroscopy were employed to study the corrosion behavior in 3.5 wt% NaCl aqueous solution. Composite coating with CPANI/LDH exhibited excellent anticorrosion performance owing to the barrier and passive effect of LDH and CPANI. The optimized specimen CAPNI/LDH0.5% presents a superior barrier property during 45 d immersion compared with pure epoxy coating.